Hubungan Pengetahuan dan Sikap Ibu dalam Pemberian Gizi Seimbang dengan Kejadian Stunting pada Balita - Yulidar, Elfina (UKInstitute, 2024)
Cases of stunting under five currently have the highest number when compared to other forms of malnutrition. Parents have an important role in fulfilling the nutrition of toddlers, especially the role of a mother as someone who is often with toddlers. If a mother has good knowledge, of course it will also affect a good attitude in fulfilling toddler nutrition. The purpose of this study was to determine the relationship between knowledge and attitudes of mothers in providing balanced nutrition with the incidence of stunting in toddlers at the Cisungsang Community Health Center, Lebak Regency in 2023. The research design used a correlational method with a cross-sectional approach with data collection tools using questionnaires and analyzed univariately and bivariately. The sample in this study amounted to 60 respondents. The results showed that almost all 49 toddlers (81.7%) did not experience stunting, most of the respondents 39 (65.0%) had good knowledge and most of the respondents 37 (61.7%) had a positive attitude. The statistical test results showed that there was a relationship between knowledge in providing balanced nutrition and the incidence of stunting in toddlers with a value (p-value = 0.001) and there was a relationship between the mother's attitude in providing balanced nutrition with the incidence of stunting in toddlers with a value (p-value = 0.002). It is hoped that health workers will be able to provide education to the public about the nutritious food needed so that the incidence of stunting can be reduced with promotive, preventive and curative efforts from health workers.